L’impact des verbes d’action sur la compréhension des consignes de lecture des collégiens en FLE - Ghezal , Nadra (Journal of Social Sciences and Humanities, 2021)
This study adress one of the difficulties of reading comprehension, namely the understanding of instructions; Hence the interest given to the comprehension / misunderstanding of action verbs by students in the context of French as a foreign language, when the teacher's instructions are formulated. Indeed, in order to evaluate the reading-comprehension activity, the teacher addresses questions to the students, offering them more or less appropriate instructions. The texts constituting these instructions, which encourage action, can be a source of problems for them; this is why we interviewed 100 middle school students in 4th year, with the aim of determining their way of acting in the face of reading comprehension instructions and thus highlighting their deficiencies in vocabulary. Under these conditions, this study proposes to examine the difficulties experienced by depository processors. It is believed that this examination can help them gain access to meaning, not impede them